Development of Group Theory Module for User Classes Online Flipped Classroom Learning Model Loaded with Unity of Sciences - Agus Wayan Yulianto; Prihadi Kurniawan (Jurnal Pendidikan Matematika IKIP Veteran Semarang, 2022)
This study aims to develop a Group Theory Module for the User Class of the Online Flipped Classroom Learning Model with Unity of Sciences based on the need for modules in the introductory algebraic structure one course that can increase student activity in online lectures and include the Unity of Sciences breath. This research is development research using the ADDIE development model (Analysis, Design, Development, Implementation, Evaluation) to get the Group Theory Module for the User Class of the Flipped Classroom Online Learning Model with Unity of Sciences. The results of this study are the Group Theory Module for the User Class of the Flipped Classroom Online Learning Model with Unity of Sciences which contains the title page, learning objectives that are by the RPS, material arranged in 12 chapters, student activity sheets included in the initial or final activity in each topic/chapter, Unity of Sciences content in several chapters, guidelines for independent student activities (listening to material delivered through learning videos), and practice questions. Based on the validation results, the group theory module for the user class of the online flipped classroom learning model containing Unity of Sciences has a validity rate of 88%, which is included in the valid criteria and can be used with revisions. Based on the evaluation results at the final stage of the study, it was found that the group theory module for the user class of the online flipped classroom learning model containing Unity of Sciences was at a value of 87%, which was included in the efficient criteria and included in the effective criteria with a quality of 67%. Keywords: flipped classroom, textbook development, unity of sciences.